Clinical analysis of 96 patients with intraorbital foreign bodies: A 10-year retrospective study - You, Yayan; Wang, Xinghua; Cheng, Shengnan; Zhu, Ru; Wang, Bowen; Li, Shuang; Jiang, Fagang (Frontiers in Medicine, 2022)
Introduction: To investigate the clinical manifestations, diagnosis, and surgical treatment of intraorbital foreign bodies (IOFBs). Methods: Ninety-six patients with IOFBs were enrolled from Wuhan Union Hospital between January 2011 and January 2021. Demographic and clinical information were extracted, including gender, age, ocular laterality, cause and entrance of the trauma, material, size and quantity of foreign body, visual function, ocular complications, imaging findings and surgical intervention. The patients were separated into two groups according to the time range, group A (from January 2011 to December 2015, n=39) and group B (from January 2016 to January 2021, n=57). Results: The 96 patients (81 men, 15 women) were aged 1.6–76 years with a median age of 39.5 years. Forty-five patients (46.9%) with IOFBs were caused by work injuries. As for the visual impairment, 3 patients (3.3%) present severe and 39 patients (42.4%) present blindness. The majority of foreign bodies were metals (44.8%), followed by woods (26.0%). Computed tomography (CT) and magnetic resonance imaging (MRI) were performed on 89 (92.7%) and 21 (21.9%) IOFBs patients, respectively, in which the detection rate was 80.9% for CT, and 81.0% for MRI. Of the 25 patients of intraorbital wooden foreign bodies (IOWFBs), the utilization and detection rates of CT and MRI were higher in group B than in group A, with a significant difference in MRI utilization and detection rates between the two groups (both P<0.05). MRI had considerably greater IOWFBs detection rates than CT, with a significant difference between the two techniques in the detection rate of overall and group B (both P<0.05). In IOFBs and IOWFBs, the detection rate of initial surgery in group B was significantly higher than that in group A (both P < 0.05). Although in IOWFBs, with a reoperation rate as high as 40.0%, the reoperation rate of IOWFBs in group B was significantly lower than that in group A (P<0.05). Conclusion: IOFBs were mainly caused by work-related injuries and might lead to serious visual impairment. The application and detectability of MRI in IOWFBs improved in recent years, and MRI presented better detectability than CT in the diagnosis of IOWFBs.